2021
DOI: 10.3390/buildings11090409
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Computer Vision in Monitoring the Unsafe Behavior of Construction Workers: Current Status and Challenges

Abstract: The unsafe behavior of construction workers is one of the main causes of safety accidents at construction sites. To reduce the incidence of construction accidents and improve the safety performance of construction projects, there is a need to identify risky factors by monitoring the behavior of construction workers. Computer vision (CV) technology, which is a powerful and automated tool used for extracting images and video information from construction sites, has been recognized and adopted as an effective con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Zhou et al. (2020) and Liu et al. (2021) found that rapid construction projects benefit from unique modular design, concerted work of workers and a range of advanced technologies such as BIM, modular construction, 5G communication and computer vision technology, which can be applied to targeted interventions of construction project risks and improve the safety performance of construction projects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al. (2020) and Liu et al. (2021) found that rapid construction projects benefit from unique modular design, concerted work of workers and a range of advanced technologies such as BIM, modular construction, 5G communication and computer vision technology, which can be applied to targeted interventions of construction project risks and improve the safety performance of construction projects.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of COVID-19 presents an opportunity for the construction industry to adopt smart technologies, such as building information modeling (BIM), so as to quickly provide project information. Zhou et al (2020) and Liu et al (2021) found that rapid construction projects benefit from unique modular design, concerted work of workers and a range of advanced technologies such as BIM, modular construction, 5G communication and computer vision technology, which can be applied to targeted interventions of construction project risks and improve the safety performance of construction projects. Pav on et al (2020) proposed an infrastructure management system based on BIM.…”
Section: Opportunities For the Construction Industry In The Context O...mentioning
confidence: 99%
“…There is also a great deal of psychological pressure on employees to be more compliant with the rules [ 33 ]. Many studies have demonstrated that suppressing unsafe behavior can be effective in improving safety performance [ 34 , 35 , 36 ], and social opinions can serve as effective external factors to influence safety performances.…”
Section: Methodsmentioning
confidence: 99%
“…Shin et al (2021) developed a computer-vision-based method to count rebar, one of the most important materials in ferro-concrete structures, quickly and precisely [33]. Computer-vision-based machine-learning is used for tracking the number of site workers and the wearing of safety helmets, which is an important site safety management factor, along with material maintenance [36,37]. As summarized in Table 1, computer-vision-based AI technologies are not restricted to the lab, but are recognized for usability, thus positioning them as one of the common technologies on site [32,[38][39][40].…”
Section: Artificial Intelligence (Ai) In the Construction Industrymentioning
confidence: 99%